Climate change discourse in Russia past and present - Poberezhskaya, Marianna; Ashe, Teresa (Routledge focus on environment and sustainability, 2019)
This book explores the development of climate change discourses in Russia. It contributes to the study of climate change as a cultural idea by developing the extensive Anglophone literature on environmental science, politics and policy pertaining to climate change in the West to consider how Russian discourses of climate change have developed. Drawing on contributors specialising in numerous periods, regions, disciplines and topics of study, the central thread of this book is the shared attempt to understand how environmental issues, particularly climate change, have been understood, investigated and conceptualised in Soviet and post-Soviet Russia. The chapters aim to complement work on the history of the discursive political construction of climate change in the West by examining a highly contrasting (but intimately related) cultural context. Russia remains one of the world's largest greenhouse gas emitters with one of the most carbon-intensive economies. As the world begins to suffer the extreme consequences of anthropogenic climate change, finding adequate solutions to global environmental problems necessitates the participation of all countries. Russia is a central actor in this global process and it, therefore, becomes increasingly important to understand climate change discourse in this region. Insights gained in this area may also be illuminating for examining environmental discourses in other resource rich regions of the world with alternative economic and political experiences to that of the West (e.g. China, Middle East). This book will be of great interest to students and scholars of Russian environmental policy and politics, climate change discourses, environmental communication and environment and sustainability in general